Cell characteristics of epoxy resin foamed by step temperature-rising process using supercritical carbon dioxide as blowing agent. (March 2018) - Lyu, Jiaxun; Liu, Tao; Xi, Zhenhao; Zhao, Ling
A temperature-rising batch foaming process with supercritical carbon dioxide (ScCO2 ) as blowing agent was used to prepare epoxy resin foams consisting of diglycidyl ether of bisphenol A and m-xylylenediamine. The dissolution and diffusion behaviors of CO2 in pre-cured epoxy resin were investigated, as well as the parameter effect of CO2 saturation step and foaming step on the cell characteristics. It was proved that closed-cells could be generated for CO2 unsaturated samples and the cell characteristics with the same dissolved CO2 concentration were similar. The merged and cracked bubble morphologies were usually obtained for CO2 -saturated epoxy resin samples. With increasing CO2 concentration from 0.021 g CO2 /g epoxy resin to 0.061 g CO2 /g epoxy resin in the unsaturated samples, the cell size increased from 170.2 µm to 262.6 µm and the cell density decreased from 6.8 × 10 5 /cm 3 to 3.1 × 10 5 /cm 3 . Bubble nucleation and growth occurred simultaneously with curing reaction in temperature-rising step. As the final foaming temperature increased from 60℃ to 120℃, the cell size of samples with dissolved CO2 concentration of 0.021 g CO2 /g epoxy resin increased from 172.7 µm to 369.0 µm, while the cell density first increased from 6.8 to 7.3 and then decreased to 3.5. The cell size of samples with CO2 concentration of 0.031 g CO2 /g epoxy resin increased from 145.3 µm to 180.5 µm with foaming time from 5 min to 20 min, but changed slightly when curing reaction almost finished and CO2 was depleted after 20 min.